Corridor talk to culture history : public anthropology and its consequences - Darnell, Regna; Gleach, Frederic W. (Frederic Wright), 1960- (Histories of anthropology annual, 2015)
The Histories of Anthropology Annual series presents diverse perspectives on the discipline's history within a global context, with a goal of increasing awareness and use of historical approaches in teaching, learning, and doing anthropology. Critical, comparative, analytical, and narrative studies involving all aspects and subfields of anthropology are included. This ninth volume of the series, Corridor Talk to Culture History showcases geographic diversity by exploring how anthropologists have presented their methods and theories to the public and in general to a variety of audiences. Contributors examine interpretive and methodological diversity within anthropological traditions often viewed from the standpoint of professional consensus, the ways anthropological relations cross disciplinary boundaries, and the contrast between academic authority and public culture, which is traced to the professionalization of anthropology and other social sciences in the nineteenth century. Essays showcase the research and personalities of Alexander Goldenweiser, Robert Lowie, Harlan I. Smith, Fustel de Coulanges, Edmund Leach, Carl Withers, and Margaret Mead, among others.